Use of Marugoto teaching materials for Communication Science Department students at Pakuan University to increase motivation to learn Japanese - Karyati, Alo (Universitas Dian Nuswantoro, 2024)
This research discusses the using Marugoto teaching materials among Pakuan University Communication Science study program students. Recently, the number of Japanese language learners in Indonesia has increased. As the number of students increases, there is a need for teaching materials that can make it easier for students to learn. The formulation of the problem in this research is: (1) Can the use of Marugoto teaching materials for Communication Science Study Program students increase motivation to learn Japanese? (2) What are the opinions of Communication Science Study Program students regarding learning Japanese using Marugoto teaching materials? The aims of this research are: (1) to determine the use of Marugoto teaching materials for Communication Science Study Program students to increase motivation to learn Japanese, (2) to find out the opinions of Communication Science Study Program students regarding learning Japanese using Marugoto teaching materials. The research method used is descriptive qualitative. The research subjects were students of the communication science study program concentrating on broadcasting and journalism. Data collection techniques were via Google form, and analyzed qualitatively descriptively. The results of this research show an increase in motivation to learn Japanese.